Construction of Ag-modified ZnO–CeO2 2D-1D S-scheme heterojunction photocatalyst with phenomenal photocatalytic performance for H2 evolution. (1st June 2023) - Ahmad, Irshad; Shukrullah, Shazia; Naz, Muhammad Yasin; Alsaif, Faisal Khalid; Alsulamy, Sager; Khan, Yasin; Khalid, N.R.; Khan, Waheed Qamar
Abstract: The rational design of S-scheme heterojunctions is a promising strategy to boost the spatial separation of photocarriers and optimize the stability of the heterosystem. Herein, we successfully designed a 2D-1D ZnO–CeO2 –Ag plasmonic heterosystem containing ZnO nanosheets and CeO2 nanorods through the solvothermal process. The ZnO–CeO2 –Ag exhibits the maximum photocatalytic H2 evolution rate of 31420 μmol h −1 g −1 under simulated sunlight exposure, which is about 55 and 14 times superior to pure ZnO and CeO2, respectively. The notably high photocatalytic efficiency of ZnO–CeO2 –Ag is primarily assigned to the design of plasmonic S-scheme heterosystem. This heterosystem promotes visible light absorption due to LSPR phenomenon, which enhances the specific surface area and facilitates the built-in electric field-derived S-scheme separation and transference of photocarriers. The H2 evolution activity is also examined by varying different parameters, including catalyst dose, initial pH, nature and quantity of sacrificial reagent, and process time. The H2 evolution rate of ZnO–CeO2 –Ag for consecutive cycles confirmed its high stability and reusability. This research paves the way for the design of possible heterojunction photocatalysts for energy production and environmental remediation.